LF2OH: Learning Program in Enhancing Financial Literacy for Students - Hari Wahyono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Financial technology advancement has both positive and negative impacts on society. For generation Z who have not worked, financial technology's convenience may create financial problems, both for themselves and their families, considering that their financial source comes from their parents. Therefore, there is a need to provide a learning program for financial literacy and concern for the family's financial condition. The learning program is packaged in a Learning Management System (LMS) with the name Learning Financial Literacy from Our Home (LF2OH). This study is aimed at examining the effectiveness of the learning program and testing by using the experimental method of Solomon’s four group model on 281 high school students. The test results indicate that the average gain score and post-test financial literacy of students treated with the LF2OH program are higher and significantly different than students who are taught classically without involving learning in the family environment. This proves that the learning program using LF2OH effectively improves the financial literacy of high school students.Abstrak: Kemajuan teknologi keuangan memiliki dampak positif dan negatif bagi masyarakat. Bagi generasi Z yang belum bekerja, kemudahan teknologi keuangan dapat menimbulkan masalah keuangan, baik bagi dirinya maupun keluarganya, mengingat sumber keuangannya berasal dari orang tuanya. Oleh karena itu, perlu adanya program pembelajaran literasi keuangan dan kepedulian terhadap kondisi keuangan keluarga. Program pembelajaran tersebut dikemas dalam Learning Management System (LMS) dengan nama Learning Financial Literacy from Our Home (LF2OH). Penelitian ini menguji keefektifan program pembelajaran dan pengujian dengan menggunakan metode eksperimen model empat kelompok Solomon pada 281 siswa SMA. Hasil tes menunjukkan bahwa rata-rata peningkatan nilai dan post-test financial literacy siswa yang diberi program LF2OH lebih tinggi dan berbeda dibandingkan siswa yang diajar secara klasikal tanpa melibatkan pembelajaran di lingkungan keluarga. Hal ini membuktikan bahwa program pembelajaran menggunakan LF2OH efektif meningkatkan literasi keuangan siswa SMA.